HARVESTING COST MODEL FOR SMALL TREES IN NATURAL STANDS IN THE INTERIOR NORTHWEST. - HARTSOUGH, BRUCE R. ; ZHANG, XI
REALISTIC LOGING COST MODELS ARE NEEDED FOR LONG-TERM FOREST MANAGEMENT PLANNING. DATA FROM NUMEROUS PUBLISHED STUDIES WERE COMBINED TO ESTIMATE THE COSTS OF HARVESTING SMALL TREE IN NATURAL STANDS IN THE INTERIOR NORTHWEST OF NORTH AMERICA....